(untitled) (Journal of the College of Basic Education, 2022)
We notice that the world is as if the ancient world in its last centuries was satisfied with the three giants of philosophy, or as if the city accepted the fruits of that mature thinking, so the thinking was not shaken by philosophers, so bad ones appear after Aristotle for several centuries. Today.Centuries pass with the wheel of time, then the Islamic call appears, minarets rise, mosques spread east and west, people enter the religion of God in droves, and some residents of the countries in which Islam prevailed find tranquility and tolerance that they did not experience in times of rule in which persecutions were known from the difference of sect.